Studi potensi listrik dari hembusan angin luaran air conditioner - Gian Villany Golwa; Fajar Anggara; Imam Hidayat (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
The utilization of air conditioners (AC) will consume a lot of electricity in the world. According to the predictions of the International Energy Agency (IEA) electricity consumption for AC will be the main trigger for soaring world electricity demand in 2050. Data from the Central Statistics Agency (BPS) in March 2017 showed 7.98 percent of households in Indonesia use AC. The wind speed coming out of the condenser in an AC with a capacity of 0.5-2 PK has an average speed of 4.83 m/s. This research will test the potential electricity that can be generated from air blowing from an AC with 2 types of generator prototypes. Both types of generators will be tested directly on the AC exhaust unit. The test results show that with an average wind speed of 4.83 m/s, the vertical blade generator with 12 blades installed can produce up to 7 volts, and on the horizontal blade generator with 6 coils, each coil has 300 turns, the voltage is up to 14.82 Volts. The conclusion from this research is that the horizontal blade generator is sufficient to supply electricity to the battery before consumption.